The Insight into Obstetric Care near the Front Line in Kharkiv - Lakhno, Igor (Acta medica Lituanica, 2022)
Objectives: The invasion of Russian troops into independent Ukraine has changed the humanitarian situation in the Kharkiv region. The paper is focused on the peculiarities and issues of the management of labor and delivery near the front line.Materials and methods: Totally 2030 patients were enrolled in the study. 1410 women who delivered in the second half of 2021 were enrolled in Group I. 620 women who delivered in the first half of 2022 were observed in Group II. Some patients from Group II were used for the investigation of the comparative situation during first months of 2022. 85 women who delivered in January were included in Subgroup IIA. 94 women who have completed their pregnancies and delivered in February were observed in Subgroup IIB. 67 case histories of deliveries which occurred during March were united in Subgroup Group IIC.Results: The level of anemia, uterine contractile activity in labor abnormalities, and episiotomies were surprisingly lower during wartime in March. The obtained results showed an almost similar level of obstetric complications, maternal comorbidities, and interventions during labor and delivery in all groups. The stressed environment was a possible reason for the elevation of cardiovascular disease and endocrine disorders.Conclusion: The study did not reveal any significant changes in the structure of maternal pathologies and obstetric complications during the first months of wartime near the front line. But later the levels of cardiovascular disease and endocrine disorders were found to be elevated.
Keywords: pregnancy; obstetric care; military medicine